Smartphone chronic gaming consumption and positive coping practice. Issue 2 (5th June 2017) - de Kervenoael, Ronan; Schwob, Alexandre; Palmer, Mark; Simmons, Geoff
Abstract : Purpose: Chronic consumption practice has been greatly accelerated by mobile, interactive and smartphone gaming technology devices. The purpose of this paper is to explore how chronic consumption of smartphone gaming produces positive coping practice. Design/methodology/approach: Underpinned by cognitive framing theory, empirical insights from 11 focus groups ( n =62) reveal how smartphone gaming enhances positive coping amongst gamers and non-gamers. Findings: The findings reveal how the chronic consumption of games allows technology to act with privileged agency that resolves tensions between individuals and collectives. Consumption narratives of smartphone games, even when play is limited, lead to the identification of three cognitive frames through which positive coping processes operate: the market-generated, social being and citizen frames. Research limitations/implications: This paper adds to previous research by providing an understanding of positive coping practice in the smartphone chronic gaming consumption. Originality/value: In smartphone chronic gaming consumption, cognitive frames enable positive coping by fostering appraisal capacities in which individuals confront hegemony, culture and alterity-morality concerns.